2004
DOI: 10.1021/bi048223f
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Activity of Insulin at the Receptor Interface:  Crystal Structure and Photo-Cross-Linking of A8 Analogues

Abstract: The receptor-binding surface of insulin is broadly conserved, reflecting its evolutionary optimization. Neighboring positions nevertheless offer an opportunity to enhance activity, through either transmitted structural changes or introduction of novel contacts. Nonconserved residue A8 is of particular interest as Thr(A8) --> His substitution (a species variant in birds and fish) augments the potency of human insulin. Diverse A8 substitutions are well tolerated, suggesting that the hormone-receptor interface is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 80 publications
3
41
0
Order By: Relevance
“…5E) in a semiexposed position but well away from F25. This finding supports the suggestion (36,47) that the A-chain residues V3 and T8 may contact a region of the insert domain that is peripheral to the critical site involved in contacting the B-chain residue F25. Such disparate contact points by the IR insert domain are possible given that it appears to be intrinsically disordered based on predictions with the DisProt web server (48).…”
Section: Docking Of Insulin On the L1 Domainsupporting
confidence: 85%
“…5E) in a semiexposed position but well away from F25. This finding supports the suggestion (36,47) that the A-chain residues V3 and T8 may contact a region of the insert domain that is peripheral to the critical site involved in contacting the B-chain residue F25. Such disparate contact points by the IR insert domain are possible given that it appears to be intrinsically disordered based on predictions with the DisProt web server (48).…”
Section: Docking Of Insulin On the L1 Domainsupporting
confidence: 85%
“…It should be noted that of the six substitutions studied in this work, only Phe 49 has been shown to play a role in binding to the 49 to alanine decreased IGF-I binding to IGFBP-1 80,000-fold and to IGFBP-3 15-fold. It is not known what effect the mutation to threonine reported here has on IGFBP binding.…”
Section: A17mentioning
confidence: 68%
“…2). This position is believed to introduce favorable and unfavorable interactions at the edge of the IR and has recently been analyzed in regard to receptor binding (49). Analysis of a photoactive A8 analogue showed that it exhibited efficient cross-linking to the insert in the second fibronectin type III domain of the IR that cooperates (probably in trans (50)) with the L1 domain to create binding site 1.…”
Section: A17mentioning
confidence: 99%
“…At position B8 (occupied in native insulin by an invariant Gly with a positive angle) (33), only the D-isomer was prepared. The synthesis and characterization of protoprobes at positions A1, A3, A21, B0, B16, B24, and B25 have been described previously (6,17,25,26,34,35).…”
Section: Methodsmentioning
confidence: 99%